Social actors in the territorial planning and management of local governments in Peru - González-Acuña, Víctor Humberto (2022)
This research examined the importance of social actors in the territorial planning and management of local governments in Peru. For this purpose, a systematic review was used to analyze forty-eight publications on the topic of study from the last five years. Currently, legal norms on urban planning are given at a national level, despite the fact that the problems are different in each local government, thus generating social conflicts in the management and administration of the territories. These problems are caused by the lack of a transversal territorial planning in all sectors, which must include general guidelines to be developed by each local government according to its physical and bioclimatic characteristics. The main conclusion of the study is that all local governments face challenges when planning their territories and, consequently, in zoning and land use for future constructions in different sectors.